Eosinophils promote corneal wound healing via the 12/15‐lipoxygenase pathway. Issue 9 (28th July 2020) - Ogawa, Mamoru; Ishihara, Tomoaki; Isobe, Yosuke; Kato, Taiga; Kuba, Keiji; Imai, Yumiko; Uchino, Yuichi; Tsubota, Kazuo; Arita, Makoto
Abstract: Lipid mediators play important roles in regulating inflammatory responses and tissue homeostasis. Since 12/15‐lipoxygenase (12/15‐LOX)‐derived lipid mediators such as lipoxin A4 (LXA4 ) and protectin D1 (PD1) protect against corneal epithelial cell damage, the major cell types that express 12/15‐LOX and contribute to the corneal wound healing process are of particular interest. Here, we found that eosinophils were the major cell type expressing 12/15‐LOX during the corneal wound healing process. Eosinophils were recruited into the conjunctiva after corneal epithelium wounding, and eosinophil‐deficient and/or eosinophil‐specific 12/15‐LOX knockout mice showed delayed corneal wound healing compared with wild‐type mice. Liquid chromatography‐tandem mass spectrometry (LC‐MS/MS)‐based mediator lipidomics revealed that a series of 12/15‐LOX‐derived mediators were significantly decreased in eosinophil‐deficient mice and topical application of 17‐hydroxydocosahexaenoic acid (17‐HDoHE), a major 12/15‐LOX‐derived product, restored the phenotype. These results indicate that 12/15‐LOX‐expressing eosinophils, by locally producing pro‐resolving mediators, significantly contribute to the corneal wound healing process in the eye.